A self-doping conductive polymer hydrogel that can restore electrical impulse propagation at myocardial infarct to prevent cardiac arrhythmia and preserve ventricular function. (February 2020) - Zhang, Chongyu; Hsieh, Meng-Hsuan; Wu, Song-Yi; Li, Shu-Hong; Wu, Jun; Liu, Shi-Ming; Wei, Hao-Ji; Weisel, Richard D.; Sung, Hsing-Wen; Li, Ren-Ke
Abstract: Following myocardial infarction (MI), necrotic cardiomyocytes (CMs) are replaced by fibroblasts and collagen tissue, causing abnormal electrical signal propagation, desynchronizing cardiac contraction, resulting in cardiac arrhythmia. In this work, a conductive polymer, poly-3-amino-4-methoxybenzoic acid (PAMB), is synthesized and grafted onto non-conductive gelatin. The as-synthesized PAMB-G copolymer is self-doped in physiological pH environments, making it an electrically active material in biological tissues. This copolymer is cross-linked by carbodiimide to form an injectable conductive hydrogel (PAMB-G hydrogel). The un-grafted gelatin hydrogel is prepared in a similar manner as a control. Both test hydrogels not only provide an optimal matrix for CM adhesion and growth but also maintain CM morphology and functional proteins. The conductivity of PAMB-G hydrogel is ca . 12 times higher than that of gelatin hydrogel. Microelectrode array analyses reveal that a heart placed on the PAMB-G hydrogel has a higher field potential amplitude than that placed on the gelatin hydrogel and can pass current from one heart to excite another heart at a distance. The injection of PAMB-G hydrogel into the scar zone following an MI in a rat heart improves electrical impulse propagation over that in a heart that has been treated with gelatin hydrogel, and synchronizes heart contraction, leading to preservation of the ventricular function and reduction of cardiac arrhythmia, demonstrating its potential for use in treating MI.